The position of the Arab League on the Palestinian war with the Zionist entity )Hamas movement as a model( (Journal of the College of Basic Education, 2023)
The research aims to follow up the most important historical stations that present the characteristics of the relationship between the Arab League and the patterns of the Arab-Israeli conflict during the second half of the twentieth century and the beginning of the third millennium, specifically the war of Hamas movement with the Zionist entity , which went through many stages of policies and procedures in the context of the Arab efforts aimed at finding a solution. We do not exclude those decisions in the files of the Arab League from studying the issue of Jerusalem, which it dealt with in an inseparable manner from the Palestinian issue in general.